Associations between polymorphisms of LAP3 and SIRT1 genes with clinical mastitis and milk production traits in Sahiwal and Karan Fries dairy cattle. Issue 6 (5th September 2022) - Worku, Destaw; Gowane, G. R.; Mukherjee, Anupama; Alex, Rani; Joshi, Pooja; Verma, Archana
Abstract: Background: Bovine mastitis continues to remain as the most challenging disease in dairy cattle, as a result improvement of selection methods has great economic relevance while a deeper understanding of the genetic mechanisms regulating milk production traits and mastitis is of general scientific interest. Objectives: This study aimed to evaluate the association of SNPs of the LAP3 and SIRT1 genes with estimated breeding values (EBVs) of milk production traits and clinical mastitis in dairy cattle of Indian origin. Methods: DNA samples from 263 animals (Sahiwal and Karan Fries cattle) were genotyped by PCR‐RFLP to assess their pattern of genetic variation. EBVs of milk production traits and phenotypic records of incidences of clinical mastitis were used for association analysis. Results: A total of 9 SNPs were identified, including three (rs110932626: A>G, rs716493845: C>T and rs43702363: C>T) in intron 12, four (g.24904G>C, rs110839532: G>T, rs43702361: T>C and rs41255599: C>T) in exon 13 and within 3'UTR of LAP3 gene and two (rs110250233: G>A and rs42140046: C>G) in the promoter region of SIRT1 gene. Eight of these identified SNPs were chosen for subsequent genotyping and association analyses. Association analysis revealed that SNP rs41255599: C>T was significantly associated with lactation milk yield, 305‐day milk yield, 305‐day fat yield, 305‐day solid not fat yield, lactation length and incidence of clinical mastitis ( p < 0.05) in Sahiwal cattle. For Karan Fries cattle, two SNPs including rs110932626: A>G and rs43702363: C>T showed significant association with 305‐day milk yield. Conclusion: Overall, these findings provide evidence for association of the LAP3 gene with milk production traits and clinical mastitis in dairy cattle, indicating the potential role of LAP3 variants in these traits. Abstract : This study conducted to identify genetic variants in LAP3 and SIRT1 genes and to test the association between these variants and milk production traits and clinical mastitis in dairy cattle. Association analysis revealed that genetic variants in LAP3 gene had significant effect on milk yield traits and clinical mastitis.